Improving service-learning practice : research on models to enhance impacts - Callahan, Jane; Root, Susan, 1948-; Billig, Shelley (Advances in service-learning research ;, 2005)
This fifth book in the Advances in Service-Learning Research series continues to expand the discussion of service-learning research and practice. The chapters were selected through a refereed, blind-review process from papers presented at the 4th Annual International K-H Service-Learning Research Conference held October 2004 in Greenville, South Carolina. The chapters focus on topics that address a variety of issues in higher education and teacher education and are organized into four sections.